Obsidian Evidence of Interaction and Migration from the Mesa Verde Region, Southwest Colorado. Issue 4 (20th October 2011) - Arakawa, Fumiyasu; Ortman, Scott G.; Shackley, M. Steven; Duff, Andrew I.
Abstract : A growing body of evidence demonstrates that ancestral Pueblo people living in the central Mesa Verde region of the U.S. Southwest maintained long-distance contacts with other Pueblo peoples. Questions of Pueblo interactions through time and across space have traditionally been addressed using ceramic sourcing data. This research uses obsidian source data to argue that, from A.D. 600 to 920, residents of the central Mesa Verde region obtained obsidian from throughout the U.S. northern Southwest, but that from A.D. 1060 to 1280 they acquired obsidian almost exclusively from the Jemez Mountains area of north-central New Mexico. In addition, importation of obsidian from the Pajarito Plateau increased during the period of population decline in the Mesa Verde region, and population expansion on the Pajarito. Characteristics of the obsidian assemblage from central Mesa Verde region sites also suggest that Jemez obsidian entered the region primarily in the form of finished arrows, arrow points, and arrow-point preforms. We argue that these patterns reflect return migration by early immigrants from the Mesa Verde region to the northern Rio Grande, an early stage in the development of a migration stream between the two regions.